THE PROBLEM OF DEVELOPMENT OF PROFESSIONAL AND PEDAGOGICAL TRAINING OF PRE-CONTRACTION MILITARY EDUCATION TEACHERS (Scientific journal of the Fergana State University, 2024)
This article examines the problem of the development of professional and pedagogical skills of a teacher of pre-conscription education. the process of modernization of education, effective organization of professional activity, striving for the development of the most modern knowledge, search and receipt of information, study of best practices, textbooks, content of pedagogical activity, personality and capabilities of the student, striving to achieve the level of pedagogical skill, methodological foundations of standardization of the process of achieving success in pedagogical activity, modeling of professional pedagogical activity, training of future teachers of military education, knowledge, received from the ancestors, along with the secrets of military and educational activities of students, based on ethics, customs, national and cultural values, experience, self-determination and formation of potential and worldview, the general professional and personal composition of teachers of military education before the upcoming conscription; features of professional and pedagogical activity, technologies for the implementation of organizational and pedagogical conditions, motivational professional and pedagogical training, acquisition and realization of one's knowledge, skills, attitude to future professional activity and striving for success, creativity and features of educational activities that contribute to the development of creativity, the ability to creatively respond to the problems of the praxeological profession, professionalism, knowledge, skills and abilities, professional self-awareness, the use of modern educational technologies in teaching academic subjects "General Military Regulations" and "Pure learning", a technological approach, "Flipped Class" technology for training future military and teaching staff and the organization of educational.